CHARACTERISTICS AND TECHNIQUES OF CRIMINAL INVESTIGATION OF COMPUTER FINANCIAL CRIME - Nikolovska, Svetlana; Gjosheva-Krsteski, Marija (Horizons - International Scientific Journal, 2021)
Cyber crime is a serious crime that causes not only financial consequences, but also distrust in the business operations of legal entities and distrust of clients towards financial institutions - banks. Forensic research is a procedure of applying tactics of obtaining information, their analysis, assessment of the application of legal measures and technical methods and means in order to clarify and provide evidence, to initiate a procedure. The legislator envisages legal measures and actions, but their application is conditioned by the professional and professional approach of the criminal officers who build and apply appropriate tactics and techniques based on scientific knowledge, but also practical experience. This is the subject of study in this paper in order to obtain indicators on the basis of which strategies will be built for protection of cyber financial data, as well as strengthening the detective function of the police as a competent body for combating this crime.